إدارة المعرفة التسويقية وأثرها على الإبتكار التسويقي -دراسة تطبيقية في بعض وكالات موبيليس- - قدري, لويزة; راهم, فريد (جامعة الوادي - University of Eloued, 2022)
This study aimed to identify the reality of the business practices of service organizations to the process of knowledge management and its relationship with marketing innovation, therefore the results showed that there is a positive relationship between the application of knowledge and innovation in the service And also there is a positive (R2 =0.475), , The questionnaire was a key instrument to collect data from a simple random (71) questionnaires were recived, the descriptive analytical methodology was adopted in this study
Knowledge Management and its Impact on Marketing Innovation --An applied study in some Mobilis agencies
مقال
Keywords: إدارة المعرفة التسويقية؛ عمليات إدارة المعرفة التسويقية؛ التسويق الإبتكاري